Design and development of a charging station for electric vehicles - Hui, Jia Junn. (2013)
As the world is turning towards green renewable energy, electric vehicle (EV) is gaining popularity and the big players are starting to roll out more EVs. As EV also require to recharge like their counter fossil fuel vehicle, a service industry will emerge to serve recharging needs of consumers. The charging infrastructure will make use of existing electricity production and distribution to build on an infrastructure network for charging station.